SIMULASI PENYUSUPAN LEMPENG INDO-AUSTRALIA KE LEMPENG EURASIA DI PANTAI BARAT SUMATERA BARAT - Razi, Pakhrur (Sainstek : Jurnal Sains dan Teknologi, 2010)
In the coastal area of west Sumatra, specially west Sumatra represent area which is gristle will of the earthquake, since in the coastal area of west Sumatra can be found plate subduction area active that is Indo-Australia plate to Eurasia plate with necromancy average angle is 31,330 and average speed 6-7 cm/year, and sesar area that spread in the as far as Sumatra Island that caused by necromancy sideway Indo-Australia plate to Eurasia. Aims of this research is creating visualization imaging subduction of   Indo-Australia plate toEurasia and change of surface morphology. Method of this research is Development research method or R&D, Data of this research based on old research (Akmam, 2006) and visual imaging from Natawijaya (2005). This simulatin maked using 3D max software, google earth, photoshop, and other software, that result it packet in DVD form. Keywords: simulation, subduction, subduction coastal west sumatera